Exploring spatial variations and risk factors associated with cesarean section delivery in Bangladesh - Islam, Md. Saiful; Bhuiyan, Md. Junayeth; Miah, Md. Sharif; Rashid, Md. Mamunur (International Journal of Public Health Science (IJPHS), 2025)
This study was to explore the spatial variations and risk factors of cesarean delivery in Bangladesh. We used the Bangladesh Demographic and Health Survey (BDHS) 2017-18 data. The Getis-Ord Gi* statistic was applied to assess the hot spots and cold spots of cesarean delivery, and a multilevel logistic regression model was utilized to determine the risk factors related to cesarean delivery in Bangladesh. This study found that one-third of all births (33%; 95% CI = 30.68-34.66) delivered through cesarean section. The hot spots of cesarean delivery were in Dhaka, Khulna, Rajshahi and Rangpur divisions. The cold spots were in Barisal, Rangpur, and Sylhet divisions. Women with higher education (OR =2 .24, 95% CI = 1.49-3.36), overweight/obese women (OR = 2.07, 95% CI = 1.63–2.63) and women from Khulna division (OR = 1.87, 95% CI= 1.32–2.64) were significantly associated with cesarean section. Therefore, concentrating on factors including women’s education, partner's education, partner’s occupation, age at first birth, wealth index, women’s body mass index (BMI) status, media exposure, and divisions might play a crucial role in reducing the unnecessary cesarean section in Bangladesh.